Громадянська освіта в підготовці вчителів початкової школи: європейські практики для дизайну «Центру підтримки школи» в умовах міграційних викликів - Терепищий Сергій; Terepyshchy Sergey (Видавництво «Код», 2025)
Резюме. У статті здійснено аналіз європейських практик громадянської освіти у підготовці майбутніх учителів початкової школи з урахуванням міграційних викликів та потреб інтеграції дітей-біженців. На основі огляду сучасних наукових підходів і прикладів міжкультурної освіти розроблено концептуальну модель «Центру підтримки школи» як університетсько-шкільного осередку, що поєднує культурно чутливе вчителювання, демократичні практики в класі та цифрову громадянськість. Схема Центру відображає взаємозв’язок між підготовкою вчителя, організаційними інтервенціями та досягненням ключових результатів – безпеки, належності, участі та інтеграції учнів. Запропонована модель орієнтована на інтеграцію коротких модулів у навчальні плани підготовки вчителів, упровадження клініки вчителювання та супервізії у школах-партнерах, а також використання інструментів моніторингу й оцінювання освітнього клімату.

Abstract. This article explores European practices of citizenship education in the preparation of future primary school teachers with particular attention to the challenges posed by migration and the integration of refugee children. Based on an analysis of recent research and case studies, the author proposes a conceptual model of a «School Support Center» as an institutional hub linking universities, schools, and local communities. The model highlights three interconnected strands of teacher preparation: culturally responsive teaching, democratic classroom practices, and digital citizenship. Each strand is operationalized through modules that combine seminars, supervised micro-practices, and reflective assignments, thereby enabling student teachers to develop empathy, intercultural competence, and the ability to facilitate inclusive participation in multicultural classrooms. The scheme illustrates how the integration of these strands leads to measurable outcomes such as safety, belonging, participation, and integration for children with migration backgrounds. The article emphasizes that the implementation of a School Support Center creates opportunities for both the professionalization of teacher education and the strengthening of school resilience in contexts of war and displacement. By embedding rights-based frameworks, trauma-sensitive practices, and digital competence into teacher training curricula, universities can prepare educators not only to deliver knowledge but also to act as facilitators of democratic culture and community cohesion. The proposed model underscores the importance of cooperation between higher education institutions, schools, and local stakeholders, offering mechanisms for monitoring and evaluating progress through climate surveys, participation rubrics, and student portfolios. The practical value of this research lies in its contribution to designing sustainable institutional frameworks that equip teachers with the competencies required to support displaced learners, foster democratic values, and promote social solidarity in conditions of crisis and migration.
Civic education in primary school teacher training: european practices for designing a «School support center» in the conditions of migration challenges
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: громадянська освіта; підготовка вчителів початкової школи; культурно чутливе вчителювання; демократичні практики; цифрова громадянськість; інтеграція учнів-біженців; Центр підтримки школи